The Adjustment of Gamma-Aminobutyric Acid(A) Tonic Subunits in Huntington S Disease: From Transcription to Translation to Synaptic Levels into the Neostriatum - (:unkn) unknown (WOLTERS KLUWER MEDKNOW PUBLICATIONS, 2018)
gamma-Aminobutyric acid (GABA), plays a key role in all stages of life, also is considered the main inhibitory neurotransmitter. GABA activates two kind of membrane receptors known as GABA(A) and GABA(B), the first one is responsible to render tonic inhibition by pentameric receptors containing alpha 4-6, beta 3, delta, or pl-3 subunits, they are located at perisynaptic and/or in extrasynaptic regions. The biophysical properties of GABA(A) tonic inhibition have been related with cellular protection against excitotoxic injury and cell death in presence of excessive excitation. On this basis, GABA(A) tonic inhibition has been proposed as a potential target for therapeutic intervention of Huntington s disease. Huntington s disease is a neurodegenerative disorder caused by a genetic mutation of the huntingtin protein. For experimental studies of Huntington s disease mouse models have been developed, such as R6/1, R6/2, HdhQ92, HdhQ150, as well as YAC128. In all of them, some key experimental reports are focused on neostriatum. The neostriatum is considered as the most important connection between cerebral cortex and basal ganglia structures, its cytology display two pathways called direct and indirect constituted by medium sized spiny neurons expressing dopamine D1 and D2 receptors respectively, they display strong expression of many types of GABA(A) receptors, including tonic subunits. The studies about of GABA(A) tonic subunits and Huntington s disease into the neostriatum are rising in recent years, suggesting interesting changes in their expression and localization which can be used as a strategy to delay the cellular damage caused by the imbalance between excitation and inhibition, a hallmark of Huntington s disease.